Development Of Dengue Immunodiagnostic Assay By Targeting Denv Type 2 Ns1 Using Shark Single Domain Vnar Antibody - Kok, Boon Hui (2024)
Denv infection diagnosis requires early and rapid detection which is accurate and specific to provide effective treatment for the patients. However, problems such as limitations of rapid diagnostic test, antibody instability, cross-reaction among denv serotypes and other flaviviruses are causing the dengue diagnosis to be challenging. Alternatively, vnar sdab derived from shark ignar has proven some promising characteristics such as improved stability, thermostability and ability to bind on cavities or clefts hidden on targeted surface. These could possibly overcome the limitations encountered while using conventional antibodies. In this study, a potential binder namely anti-ns1 vnar-z8 was isolated from semi-synthetic shark vnar library and successfully expressed as soluble protein using e. Coli expression system. This soluble recombinant anti-ns1 vnar-z8 shown improved specificity (1.70 ± 0.11) towards denv type 2 ns1 antigen as compared to commercial anti-ns1 mab (1.17 ± 0.07). Besides, both antibodies were sensitive within the detection range of 0.03 μg/ml to 60 μg/ml. The good thermostability characteristic of anti-ns1 vnar-z8 was also proven in this study with retainment of binding affinity towards ns1 antigen after thermal treatment at various temperature (25°c to 60°c) for up to 1 week. On the other hand, the early lfa prototype was successfully developed using aunps conjugated anti-ns1 vnar-z8 protein. Throughout the prototype stability characterization,